Integrase resistance emergence with dolutegravir/lamivudine with prior HIV-1 suppression - Revollo, Boris; Viñuela, Laura; de la Mora, Lorena; García, Federico; Noguera-Julián, Marc; Parera, Mariona; Paredes, Roger; Llibre, Josep M. (Journal of antimicrobial chemotherapy, 2022)
Integrase resistance has not been reported with co-formulated dolutegravir/lamivudine in clinical trials or real-life cohorts. We aim to report, to the best of our knowledge, the first case of selection of the key integrase mutation R263K in a subject treated with this regimen started as a switch strategy with undetectable plasma HIV-1 viraemia. Clinical case report. A patient with long-term suppressed HIV-1 viraemia (<50 copies/mL) with no known risk factors for virological failure and never exposed previously to an integrase inhibitor developed virological failure (consecutive plasma HIV-1 RNA 149 and 272 copies/mL) with 322 CD4 cells/mm3 despite good treatment adherence. He was receiving the anticonvulsant clobazam, considered to have a potential weak interaction with dolutegravir, unlikely to require a dose adjustment. Plasma HIV-1 genotypic deep sequencing (Vela System) revealed the emergence of R263K (79.6%) and S230N (99.4%) mutations in the integrase region (intermediate resistance to dolutegravir, score = 30 Stanford HIVDB 9.0). The reverse transcriptase and protease regions could not be amplified due to low viral loads. PBMC DNA deep sequencing performed some months later revealed mutations M184I (14.29%) and M230I (6.25%) in the reverse transcriptase and G163R (9.77%) and S230N (98.8%) in the integrase. R263K was only found at extremely low levels (0.07%). This case illustrates that integrase resistance can emerge in patients treated with co-formulated dolutegravir/lamivudine and raises awareness of the need to carefully consider and monitor drug-drug interactions, even when regarded as having a low potential, in subjects treated with dolutegravir/lamivudine.